A comparative study between chemical and enzymatic transesterification of high free fatty acid contained rubber seed oil for biodiesel production. Issue 1 (31st December 2016) - Sebastian, Jilse; Muraleedharan, Chandrasekharan; Santhiagu, Arockiasamy
Abstract: The choice of a paramount method for biodiesel production has significance as the demand of alternative fuels like biodiesel is growing rapidly. In the present study, experimental results from chemical-catalysed as well as enzyme-catalysed methods were compared using common influencing parameters such as oil/alcohol molar ratio, catalyst concentration and reaction duration. Requirement of certain solvents to enhance the reaction rate was explained in the enzyme-catalysed transesterification reaction. Biodiesel conversion of more than 90% was attained for chemical-catalysed transesterification, whereas the conversion rate was 85% for enzyme-catalysed method. This gives the indication of further refinement in the enzyme-catalysed transesterification process. The influencing parameters and absolute results of the analysis give the impression of superiority of enzymatic transesterification method for biodiesel production from high free fatty acid-contained rubber seed oil.